The environmental impact of optimum insulation thickness for external walls and flat roofs of building in Turkey's different degree-day regions - Ucar, Aynur (Sila Science, 2009)
The optimum insulation-thickness for the flat roofs and walls of buildings energy savings over a lifetime of 10 years and payback periods are calculated for three different insulation materials and the twelve various cities from four climate zones of Turkey. Stropor, polystyrene and rockwool as insulation material are selected. In this study, it is calculated the value of the amount of the net energy savings using the P-1-P-2 method. The results show that optimum insulation thicknesses vary between 1.46 and 14.1 cm,, energy savings vary between 3.67 and 11.78 $/m(2), and payback periods vary between 2.07 and 3.25 years depending on the city and the wall type. The lowest value of optimum insulation thickness is obtained as 1.77 cm for roof 3 in Antalya, while the highest value is found as 8.16 cm in Bayburt. In this study, environmental impact of optimum insulation thickness in external walls and roofs has been investigated. It is found that when the optimum insulation thickness is used, the amount of fuel consumption and the emissions of CO2 and SO2 are decreased by 88%.
Keywords: Insulation thickness; Energy savings; Environmental impact